ECONOMIC ANALYSIS OF THE IMPLEMENTATION OF RAINWATER HARVESTING SYSTEMS IN HOMES - da Fonseca, Patrícia Cecília Rodrigues Mapa (Revista Sistemática, 2025)
The global water crisis, aggravated by climate and population factors, drives the search for sustainable solutions to optimize water use. Among these alternatives, rainwater harvesting emerges as an efficient strategy to reduce dependence on conventional sources and minimize supply costs. Studies show that up to 40% of residential demand can be met by this source, providing economic and environmental benefits. However, the feasibility of implementing these systems depends on initial investments in infrastructure and ongoing maintenance to ensure water efficiency and quality.